KOMUNIKASI POLITIK ANIES BASWEDAN MELALUI SOSIAL MEDIA TWITTER - Ashari Sakti Alim; Dian Eka Rahmawati (Jurnal Academia Praja, 2021)
Abstract This paper wants to analyze how Anies Baswedan conveyed his political communication on Twitter social media. In this contemporary era, one of the most dominant political communications is social media, where political communication plays an important role because it can have an impact on political participation, political socialization. In the political field the role of social media is very important because it contributes as openness and transparency, Anies Baswedan is one of the political actors who play social media Twitter to convey political communication while increasing its popularity. In accordance with its previous political promises of integrated transportation and ok oce program. Anies is not uncommon to convey and show the development of political promises that have been running on his Twitter social media. in disseminating information through social media Twitter has proven to be very effective because many users around the world. This study uses descriptive qualitative research methods and analyzes using the help of NVIVO12 Plus software applications. The results of this study revealed that Anies Baswedan's political communication on Twitter social media was very focused on public services in DKI Jakarta. Political communication from Anies Baswedan also received a lot of responses from his followers on his Twitter account. This can be seen from the number of retweets and mentions done to Anies Baswedan. Anies Baswedan was also quite active in conveying his political communication through Twitter social media such as notifying work programs, political branding, giving political talks that were light in nature and also related to public services in DKI Jakarta. Keywords : Political Communication, Anies Baswedan, Social Media, Twitter Abstrak Tulisan ini ingin menganalisis bagaimana Anies Baswedan dalam menyampaikan komunikasi politiknya di sosial media Twitter. Pada era kontemporer ini salah satu komunikasi politik yang paling dominan adalah media sosial, dimana komunikasi politik sangat memegang peranan penting karena bisa berdampak untuk partisipasi politik, sosialisasi politik. Dalam bidang politik peran media sosial media sangat penting karena berkontribusi sebagai keterbukaan dan transparansi, Anies Baswedan adalah salah satu aktor politik yang bermain sosial media Twitter untuk menyampaikan komunikasi politik sekaligus menaikan popularitasnya. Sesuai dengan janji politiknya terdahulu yaitu transportasi terintegrasi dan program oke oce. Anies tak jarang menyampaikan dan memperlihatkan perkembangan janji politiknya yang telah berjalan di sosial media Twitter miliknya. dalam penyebaran informasi melalui sosial media Twitter sudah terbukti sangat efektif karena banyak penggunanya diseluruh dunia. Penelitian ini menggunakan metode penelitian kualitatif deskriptif dan melakukan analisis dengan menggunakan bantuan aplikasi perangkat lunak NVIVO12 Plus. Hasil dari ini penelitian ini mengungkapkan bahwa komunikasi politik Anies Baswedan di sosial media Twitter sangat befokus pada pelayanan publik di DKI Jakarta. Komunikasi politik dari Anies Baswedan juga mendapatkan banyak respon dari pengikutnya di akun Twitter hal ini dapat dilihat dari jumlah Retweet dan mentions yng dilakukan kepada Anies Baswedan. Anies Baswedan juga cukup aktif dalam menyampaikan komunikasi politiknya melalui sosial media Twitter seperti memberitahukan program kerja, Branding politik, memberikan perbincangan politik yang sifatnya ringan dan juga terkait dengan pelayanan publik di DKI Jakarta. Kata Kunci : Komunikasi Politik, Anies Baswedan, Sosial Media, Twitter